SOURCES OF QUATERNARY POTASSIC VOLCANIC ROCKS FROM WUDALIANCHI, CHINA: CONTROL BY TRANSTENSION AT THE LITHOSPHERE–ASTHENOSPHERE BOUNDARY LAYER - S. V. Rasskazov; I. S. Chuvashova; Yi-min Sun; Chen Yang; Zhenhua Xie; T. A. Yasnygina; E. V. Saranina; Zhenxing Fang (Геодинамика и тектонофизика)
Introduction. Transtension is a system of stresses that tends to cause oblique extension, i.e. combined extension and strike slip. Syn-volcanic transtensional deformations of the lithosphere may provide two possible scenarios for control of magmatic processes. One scenario assumes ascending sub-lithospheric melts that mark the permeable lithosphere in a transtension area without melting of the lithospheric material; products of volcanic eruptions in such a zone show only the sub-lithospheric mantle material; components of magmatic liquids do not reveal any connection to the lithospheric structure. Another scenario yields a direct control of melting in lithospheric sources in an evolving transtensional structure. In this case, spatial-temporal changes of lithospheric and sub-lithospheric components are a direct indication of the evolving transtensional zone. In this paper, we present arguments in favor of the transtensional origin of the lithosphere-derived melting anomaly along the Wudalianchi volcanic zone, which are based on the study of components in the rocks sampled from the volcanic field of the same name.Analytical methods. Trace elements were determined by ICP–MS using a mass-spectrometer Agilent 7500ce and isotopes using a mass-spectrometer Finnigan MAT 262. The methods used were described in the previous papers by Rasskazov et al. [2011] and Yasnygina et al. [2015]. Major oxides were measured by “wet chemistry”.Structural setting of the Wudalianchi zone. This zone extends north-south for 230 km at the northern circuit of the Songliao basin, subsided in the Late Mesozoic – Early Cenozoic (Fig. 1).Timing of volcanism and variations of K2O contents in rocks from the Wudalianchi zone. Rocks, dated back to the Pliocene and Quaternary, show the stepwise increasing K2O content interval along the Wudalianchi zone from the southernmost Erkeshan volcanic field (5.6–5.8 wt %) to the northernmost Xiaogulihe-Menlu volcanic field (2.0–9.5 wt %) (Fig. 2).Spatial-temporal clustering of volcanoes in the Wudalianchi field. In terms of the general Quaternary evolution of volcanism in Asia [Rasskazov et al., 2012], spatial-temporal distribution and compositional variations of volcanic products, we distinguish three time intervals of the volcanic evolution: (1) 2.5–2.0 Ma, (2) 1.3–0.8 Ma, and (3) <0.6 Ma. The Central group of volcanoes showed persistent shifting of eruptions from Wohushan (1.33–0.42 Ma) to Bijiashan (0.45–0.28 Ma) to Laoheishan (1720–1721, possibly earlier) to Huoshaoshan (1721) (Figs 3, 4, 5). No spatial-temporal regularity of eruptions in volcanoes of the Erkeshan field and Western and Eastern groups of the Wudalianchi field reflected background activity.Sampling. Representative sampling of rocks from the Wohushan–Huoshaoshan volcanic line was aimed to identify changing geochemical signatures along the whole volcanic line and in the course of eruptions in each volcano (Figs 3, 6, 7). For comparisons, the background volcanoes were also sampled.Silica and alkalis oxides. On the total alkalis–silica (TAS) diagram (Fig. 8), data points of background rocks are distributed along the dividing lines between highly and moderately alkaline series mainly in tephriphonolite and trachyandesite fields with a few samples in the phonotephrite field. Background rocks from some volcanoes (e.g. Yaoquanshan and Weishan) are highly alkaline (phonotephrites and tephriphonolites). Background rocks from other volcanoes (Longmenshan, Jiaodebushan etc.) are moderately alkaline (mostly trachyandesites). In background rocks, Na2O+K2O range from 8.6 to 9.7 wt %, SiO2 from 51.6 to 55.0 wt %. Phonotephrites from the Erkeshan field are comparable with the Wudalianchi background rocks of this type.Data points of rocks from the Central group of volcanoes are also distributed along the discriminating line of highly and moderately alkaline series, mainly in the phonotephrite and trachyandesite fields. Almost all samples from the first volcano (Wohushan) fall within the data field of background rocks. Rock compositions of the second and third volcanoes (Bijiashan and Laoheishan) changed on each of them from similar to the background to the ones distinguished by the lower silica and alkalis contents. On the Bijiashan volcano, eruptions were exhibited by trachyandesites of a lava shield and by basaltic trachyandesites and phonotephrites of a volcanic cone. The trachyandesites were comparable to the background rocks, the basaltic trachyandesites and phonotephrites differed from them. On the Laoheishan volcano, rocks were subdivided into three groups: (1) basaltic trachyandesites and phonotephrites, (2) trachyandesites, and (3) phonotephrites. The first group was recorded in pyroclastic material from the late volcanic cone and lavas from the northern bocca, the second group in pyroclastic material from the northwestern edge of the late crater, and the third group in bombs from its southwestern edge. On the fourth volcano (Huoshaoshan), rocks are basaltic trachyandesites and phonotephrites.In terms of Na2O, K2O, and SiO2 contents, peripheral lavas of volcanic fans in the Bijiashan, Laoheishan, and Huoshaoshan volcanoes were close to background rocks. The contents of these oxides, differed from the background signatures, characterize rocks from volcanic cones in a linear progression that demonstrates the transition from compositions of the Wohushan volcano, close to background ones, through the intermediate values in the Bijiashan and Laoheishan volcanoes to the final compositions in the Huoshaoshan volcanic cone.In the background rocks, K2O concentrations range from 4.8 to 6.0 wt % with its relative decrease in the rocks of the beginning and end of volcanic evolution. Initial lava flows with K2O contents as low as 4.0 wt % erupted along the Laoshantou – Old Gelaqiushan north-south locus from 2.5 to 2.0 Ma and in the final cone of the Huoshaoshan volcano, erupted in 1721, fell to 3.2 wt %. Since 1.3 Ma, irregular spatial-temporal distribution of volcanic activity reflected dominated background processes. Between 1.3 and 0.8 Ma, eruptions took place at the South Gelaqiushan volcano and along the west-east locus of the Lianhuashan, Yaoquanshan, West Jaodebushan, West Longmenshan volcanoes. In the last 0.6 Ma, three groups of volcanoes erupted: Western (North Gelaqiushan, Lianhuashan, Jianshan-Jianshanzi, Central (Wohushan, Bijiashan, Laoheishan, Huoshaoshan), and Eastern (Weishan, East Jaodebushan, Xiaogoshan, West and East Longmenshan, Molabushan). Background eruptions continued in the Western and Eastern groups, whereas the Central group displayed stepwise shift of activity from the southwest to the northeast. Under such a regular volcanic evolution, relative reduction of K2O abundances took place in final eruption products of the Huoshaoshan volcano (Fig. 9).Other major oxides. Changes of rock compositions along the Wohushan-Huoshaoshan line, from the close to the background signatures at the first volcano (Wohushan) through the contrast major oxide contents at the Bijiashan and Laoheishan edifices to notably different from the background ones at the Huoshaoshan cone, are illustrated further by diagrams of SiO2 vs. MgO, Al2O3 vs. MgO, CaO vs. MgO, and P2O5 vs. MgO (Figs 10, 11).Trace elements. No sufficient difference is found between primitive mantle-normalized patterns plotted for rocks from different volcanoes (Fig. 13). Nevertheless, specific variations of rock compositions in the Central group of volcanoes close to the background and different from them are shown on the diagrams of Ni, Cr, Rb, Zr, Ba, Th, Sr, and La/Yb vs. MgO (Figs 12, 14, 15). A similar behavior was observed, on the one hand, for Rb and Zr, on the other hand, for Ba, Th, Sr, and La/Yb. In rocks from the Central group of volcanoes, which are compositionally close to the background ones, Rb concentrations increase from the first volcano (Wohushan) through the second (Bijiashan) to the third (Laoheishan). In rocks that differ from the background ones, Rb concentrations increase from the second to the fourth volcano and decrease in its final edifice. In rocks, close to the background ones, Zr concentrations decrease from the first to the second volcano and increase to the third volcano. In rocks, distinguished from background ones, relatively low concentrations of Zr at the first volcano change to elevated concentrations at the third and fourth volcanoes with relative decrease at the final Huoshaoshan edifice.Discussion. Sub-lithospheric continuum of components under East Asia comprises a material from convective mantle domain with subducted slab (paleoslab) fragments of oceanic (paleooceanic) crust as well as delaminated lithospheric blocks of orogens. Volcanic rocks from the Wudalianchi field show a sub-lithospheric end-member, which belongs to this continuum. Lithospheric components of these rocks, however, have no connection with other sub-lithospheric components. We refer the Wudalianchi rocks to a sub-lithospheric–lithospheric cluster of components from the boundary between the lithosphere and sub-lithospheric convective mantle (Fig. 17). From the comparative analysis of K2O, other major oxides, and trace elements in rocks of early and late eruption phases in the Central group of volcanoes, we infer that rocks were compositionally almost similar to the background ones in edifices of the first volcano (Wohushan), partially close to the background rocks and partly differed from them in edifices of the second and third volcanoes (Bijiashan, Laoheishan), and significantly different from the background rocks in the cone of the fourth volcano (Huoshaoshan) (Figs 18, 19). We suggest that magma generation under the Wudalianchi volcanic field was controlled by developing transtension of a layer at the base of the lithosphere that divided and shielded sources of the underlying homogeneous sub-lithospheric convective mantle and the overlying enriched heterogeneous lithosphere. The sub-lithospheric magma source had 87Sr/86Sr=0.7052, sources of the boundary shielding layer the same and lower Sr-isotopic ratios, and sources of the overlying region the same and higher ratios (Fig. 20). Through the extremely low row of data points for rocks from the Huoshaoshan volcanic cone in 87Sr/86Sr vs. 87Rb/86Sr plot, we get an estimate of about 98 Ma for the isotopic system closure at the base of the lithosphere with the initial 87Sr/86Sr apatite-related value 0.70485 and the underlying convective mantle domain with Rb/Sr=0.092 (Fig. 21). We infer that the development of transtension governed time and space of the locally introduced convective mantle component through the boundary shielding layer on background of melting enriched mantle material above the latter (Fig. 22). The 2.5–2.0 Ma local eruptions of sub-lithospheric liquids, derived from the axial part of the north-south zone of transtension, were followed by the 1.3–0.8 Ma background melts from a wider transtensional segment of the enriched lithospheric region. Afterwards, in the past 0.6 Ma, background melting of the enriched lithosphere sharply outlined edge portions of the transtensional segment, whereas simultaneous local sub-lithospheric melting propagated along a crack that originated within the boundary shielding layer due to concentrating tectonic forces at the central portion of the transtensional segment.